Praktik Pedagogi Digital Selama Pandemi Covid 19 di Universitas Islam Negeri Sunan Ampel Surabaya - Nadlir, Nadlir; Dachlan, Abdul Malick (The Sociology of Islam, 2024)
This basic research aims to map and describe digital pedagogy practices implemented during the COVID-19 pandemic at Universitas Islam Negeri Sunan Ampel Surabaya. Digital pedagogy is understood as the integration of digital technology through platformization in all learning activities, based on the argument that teaching and learning processes can be mediated by digital platforms. The study found that Learning Management Systems (Google Classroom and SINAU), communication media (Zoom, WhatsApp, and Facebook), and online learning resources (e-books, e-journals, YouTube, and educational websites) were the most familiar platforms among lecturers. Prior familiarity with these platforms before the pandemic significantly influenced their use. In contrast, platforms such as online games, collaborative tools, virtual field trips, and digital evaluation tools were less utilized. Major challenges included unequal internet access and high connectivity costs, although lecturers and students adapted psychologically without significant disruption. The study employed a mixed-method one-phase model by Creswell, using questionnaires, interviews, and observations, with 29 lecturers participating.